1996
DOI: 10.1007/bf03173738
|View full text |Cite
|
Sign up to set email alerts
|

When it comes to teaching about floating and sinking, preservice elementary teachers do not have to feel as though they are drowning!

Abstract: Preservice elementary teachers often lack science content knowledge and consequently the confidence to teach science. A three-phaseconstructivist teaching sequence was used in a graduate level elementary science methods course to improve preservice teachers' knowledge ofdensity and toprovide a model for approaching the teaching of science. Preservice teachers (N=23) showed gains in content knowledge between the pretest and aposttest administeredfifteen weeks apart, Additionally, their self-reported confidence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 10 publications
1
3
0
Order By: Relevance
“…These findings were consistent with those of other researchers in mathematics and science education who have reported that elementary teachers who give correct answers to elementary mathematics and science questions often cannot provide explanations for those answers (Greenwood, 1996;McDiarmid & Wilson, 1991). Students in the methods classes seemed to feel somewhat better about getting this question wrong, however, when it was pointed out that they were in good company since many Harvard graduates when questioned in A private universe (Schneps & Sadler, 1989) revealed many similar misconceptions or weak understandings.…”
Section: Discussionsupporting
confidence: 95%
See 2 more Smart Citations
“…These findings were consistent with those of other researchers in mathematics and science education who have reported that elementary teachers who give correct answers to elementary mathematics and science questions often cannot provide explanations for those answers (Greenwood, 1996;McDiarmid & Wilson, 1991). Students in the methods classes seemed to feel somewhat better about getting this question wrong, however, when it was pointed out that they were in good company since many Harvard graduates when questioned in A private universe (Schneps & Sadler, 1989) revealed many similar misconceptions or weak understandings.…”
Section: Discussionsupporting
confidence: 95%
“…For teachers, a conceptual knowledge beyond a tacit, unexplicated knowledge is necessary for transforming concepts into a form children can understand (McDiarmid & Wilson, 1991). At the risk of stating the obvious, teachers cannot teach for understanding what they do not understand themselves (Greenwood, 1996;Stoddart et al, 1993;Usiskin, 2002).…”
Section: Didn't Know Oxygen Could Boil! 1075mentioning
confidence: 97%
See 1 more Smart Citation
“…From the results obtained it can be concluded that previous ideas on the concept of density persist at university level. This is especially critical in the case of students who will be future primary school teachers [16] , where it is essential to master the basic concepts of the science curriculum in order to explain them adequately to their future students and identify their preconceptions. One of the causes of these results may be due to the teaching methodology received throughout their school years, so it would be necessary to propose new teaching strategies to promote truly meaningful learning.…”
Section: Discussionmentioning
confidence: 99%
“…Limited data about elementary preservice teachers' misconceptions of density display commonalities with data about K-12 students' misconceptions: like K-12 students, preservice teachers of elementary science also have difficulty relating density to buoyancy (Greenwood, 1996;Stepans, Dyche, & Beiswenger, 1988). In addition, Dawkins, Dickerson, McKinnet, and Butler (2008) found that preservice teachers of middle school science may have discrete understanding of science content but may not have connected that understanding in a coherent way.…”
Section: Misconceptions About Densitymentioning
confidence: 97%